THE ROLE OF HR COMPETENCE IN IMPROVING THE PERFORMANCE OF MSMES IN PEMATANG SERAI VILLAGE, LANGKAT REGENCY - Yanti, Eli Delvi; Sari, Maya Macia; Ardian, Noni; Hasibuan, Ratna Sari (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The role of HR Competence in developing Micro, Small and Medium Enterprises (MSMEs) is very important in improving MSME performance. This study aims to: determine the role of HR competencies in MSME actors, determine the driving factors for improving MSME performance; and knowing the inhibiting factors in improving the performance of MSMEs in Pematang Serai Village. This research is a qualitative descriptive research. The subjects of the study are MSME owners, MSME employees and customers. Data collection techniques use interviews, observations and literature studies. Data analysis techniques use qualitative descriptive analysis. The results showed that: the role of HR competence in developing MSMEs is needed who have the ability and expertise as well as good skills and innovation, so it requires special training for MSME actors. In addition to MSME owners, the government and related agencies participate in training to improve HR competence in improving MSME performance